Comparing age and sex trends of chlamydia, gonorrhoea, hepatitis and syphilis infections in Samoa in 2012 and 2017 - Robert Carney; Michaela Howells; Aaone Tanumafili; Athena Matalavea; Judith Gafa; Leausa Toleafoa Dr Take Naseria (World Health Organization Regional Office for the Western Pacific, 2020)
In Samoa, the seroprevalence rates of sexually transmitted infections other than HIV have been endemically high over the past decade, despite years of prevention programming. Odds ratio and χ2 tests were conducted to compare the rates of positivity of chlamydia, gonorrhoea, hepatitis B and C, and syphilis across age groups from 2012 and 2017 surveillance data in Samoa. Young people aged 15-19 years were significantly more likely to have a chlamydia infection compared to all other age groups in both 2012 and 2017. Hepatitis B infections were more common in males and those aged 30 and above in both 2012 and 2017. Hepatitis C had no significant differences in age, but it was more common in males in 2012 and more common in females in 2017. Older age groups (aged 45 and above) were more likely to have a positive syphilis test in both 2014 and 2017 when compared to those aged 15-24 years. The results of this analysis confirm previously observed trends in Samoa for younger age groups' prevalence of chlamydia and gonorrhoea, and for older age groups' prevalence of hepatitis B and C. But the analysis also unexpectedly found that older age groups (aged 45 and above) are more likely to test positive for syphilis (for years 2014 and 2017). Further studies are needed to assess behavioural risk factors associated with older populations in order to explain the increase in risk and to design interventions suited to this demographic.